TANGGUNG JAWAB HUKUM NOMINEE ATAS SAHAM DALAM PERJANJIAN PINJAM NAMA AKIBAT WANPRESTASI - Tiara Annisa Abdillah; Sulistyaningrum, Helena Primadianti (The Officium Nobile Journal, 2025)
Abstract The practice of nominee agreements in the ownership of shares in Limited Liability Companies has become a growing legal phenomenon alongside the increasing complexity of business and investment activities in Indonesia. In this arrangement, shares are formally registered under the nominee’s name, while the economic benefits and actual control belong to the beneficial owner. This separation between formal ownership and substantive interest often leads to legal disputes, particularly when a default occurs and questions arise regarding the legal liability of the nominee. This study aims to analyze the legal regulation of nominee share agreements and to examine the legal responsibility of nominees in the event of default. The research employs a qualitative legal method with a descriptive approach, using library research through the examination of primary legal materials such as statutory regulations and court decisions, as well as secondary legal materials including legal literature and scholarly journals. The findings indicate that Indonesian company law adheres to the principle of formal share ownership, whereby the party whose name is recorded in the shareholders register is legally recognized as the legitimate shareholder with all corresponding rights and obligations. The legal relationship between the nominee and the beneficial owner exists solely within the realm of private law and depends on the validity of the nominee agreement. If such an agreement is made for purposes contrary to statutory provisions, particularly those concerning investment regulations and transparency of share ownership, it may be declared null and void. In cases of default, the nominee may still be held legally accountable both internally to the beneficial owner and externally to third parties. This research concludes that nominee share agreements involve significant legal risks and do not provide adequate legal certainty or protection. Keywords: Nominee, Agreement, Nominee, Default Abstrak Praktik perjanjian pinjam nama (nominee agreement) dalam kepemilikan saham Perseroan Terbatas merupakan fenomena hukum yang berkembang seiring meningkatnya aktivitas investasi dan kebutuhan fleksibilitas dunia usaha di Indonesia. Dalam praktiknya, kepemilikan saham dicatat secara administratif atas nama nominee, sementara kepentingan ekonomi dan pengendalian berada pada beneficial owner. Kondisi ini menimbulkan persoalan hukum ketika terjadi wanprestasi, khususnya terkait tanggung jawab hukum nominee atas saham yang secara formal berada atas namanya. Penelitian ini bertujuan untuk menganalisis pengaturan hukum perjanjian pinjam nama saham serta menelaah tanggung jawab hukum nominee dalam hal terjadinya wanprestasi. Metode penelitian yang digunakan adalah penelitian hukum kualitatif dengan pendekatan deskriptif, melalui studi kepustakaan terhadap bahan hukum primer berupa peraturan perundang-undangan dan putusan pengadilan, serta bahan hukum sekunder berupa literatur dan jurnal ilmiah yang relevan. Hasil penelitian menunjukkan bahwa hukum perseroan Indonesia menganut prinsip kepemilikan saham secara formal, sehingga nominee yang tercatat dalam daftar pemegang saham diakui sebagai pemegang saham yang sah dengan seluruh hak dan kewajibannya. Hubungan hukum antara nominee dan beneficial owner berada dalam ranah perdata dan bergantung pada keabsahan perjanjian pinjam nama. Apabila perjanjian tersebut bertentangan dengan peraturan perundang-undangan, khususnya terkait penanaman modal dan keterbukaan kepemilikan saham, maka perjanjian dapat dinyatakan batal demi hukum. Dalam hal wanprestasi, nominee tetap dapat dimintai pertanggungjawaban hukum baik dalam hubungan internal maupun terhadap pihak ketiga. Penelitian ini menegaskan bahwa perjanjian pinjam nama saham mengandung risiko hukum yang tinggi dan tidak memberikan perlindungan hukum yang optimal. Kata Kunci: Perjanjian Pinjam Nama, Nominee, Wanprestasi